The Potential and Rationale for COX-2 Inhibitors in Lung Cancer - Krysan, Kostyantyn; Reckamp, Karen L.; Sharma, Sherven; Dubinett, Steven M. (Anti-Cancer Agents in Medicinal Chemistry, 2006)
Cyclooxygenase-2 (COX-2) overexpression is seen in many malignancies including lung cancer. Elevated tumor prostaglandin E2 (PGE2), a major COX-2 metabolite, levels have been implicated in angiogenesis, tumor growth and invasion, apoptosis resistance and suppression of anti-tumor immunity. Recent studies also revealed that PGE2 signaling may confer cells resistant to targeted growth factor receptor therapy by cross-activation of the receptor signaling pathway downstream components. Pre-clinical studies in animal tumor models have shown tumor reduction when animals are treated with COX-2 inhibitors and have demonstrated promising results when COX-2 inhibitors were combined with chemotherapeutic drugs. Based on these observations several ongoing clinical trials are currently evaluating COX-2 inhibitors as adjuvants with chemotherapy or radiation therapy in patients with advanced non-small cell lung cancer. Further understanding of the mechanisms of COX-2 in tumorigenesis and its interaction with other cellular pathways may highlight the new diagnostic, prognostic and therapeutic markers and facilitate future development of targeted strategies for lung cancer treatment and prevention.
Keywords: lung cancer